Pore structure and sorption capacity investigations of Ediacaran and Lower Silurian gas shales from the Upper Yangtze platform, China - Hu, Zhazha; Gaus, Garri; Seemann, Timo; Zhang, Qian; Littke, Ralf; Fink, Reinhard (Geomechanics and geophysics for geo-energy and geo-resources., 2021)
The shale gas potential of Ediacaran and Lower Silurian shales from the Upper Yangtze platform is assessed in this study with a focus on the contributions of clay minerals and organic matter to sorption capacity. For this purpose, a multidisciplinary assessment was carried out using petrophysical, mineralogical, petrographic and geochemical methods. In terms of TOC contents (4.2%), brittle mineral contents (68.6%) and maximum gas storage capacities (0.054–0.251 mmol/g) Ediacaran shales from this study show comparable properties to other producing shale gas systems although the thermal maturity is extremely high (VR r = 3.6%). When compared to lower Silurian shales from the same region, it is evident that (1) deeper maximum burial and (2) a lack of silica-associated preservation of the pores resulted in a relatively lower mesopore volume, higher micropore volume fraction and lower overall porosity (Ediacaran shales: 1.4–4.6%; Silurian shales: 6.2–7.4%). Gas production is therefore retarded by poor interconnectivity of the pore system, which was qualitatively demonstrated by comparing experimental gas uptake kinetics. TOC content exhibits a prominent control on sorption capacity and micropore volume for both shales. However, different contributions of clay minerals to sorption capacity were identified. This can partly be attributed to different clay types but is likely also related to burial-induced recrystallisation and different origins of illite. Additionally, it was shown that variations in sorption capacity due to incorrect estimates of clay mineral contribution are in the same range as variations due to differences in thermal maturity. Article highlights Pore structure and gas storage characteristics are evaluated for the first time for Ediacaran Shales from the Upper Yangtze platform Due to a lower free gas storage capacity and diffusivity, the Ediacaran shale can be regarded as a less favorable shale gas prospect when compared to the Silurian shale Clay mineral contribution to sorption capacity is evaluated taking clay mineralogy into consideration Maturity-related changes of organic matter sorption capacity have been discussed on the basis of a compiled data set